Sistema on-line de pedidos en la farmacia 7 de Agosto del cantón Chone - Rivera Rásury, Mauro Xavier (2013)
In order to optimize the control of orders, a web application was created in the pharmacy August 7 of Chone city, using the Web Information Systems (MIDAS), which meets each of its stages, to begin the process a survey was applied to the pharmacy customers to determine the system requirements, then followed the static content and the respective application of interfaces through DreamWeaver tool Creative Suite 5, thereafter developed the web database in MySQL through phpmyadmin 3.3.9 and Wampserver 2.1., which resulted in 11 charts. After this and, with the help of Hypertext Preprocessor (PHP) 5.2.5, dynamic functionality is added to the system. Finally confirmed the correct operation of the application performing the respective code validation testing, cross-browser compatibility, security and speed of page loading, corroborating optimization control of orders in the institution.